Chemistry of OClO in the Antarctic stratosphere - Implications for bromine - Salawitch, Ross J.; Wofsy, Steven C.; Mcelroy, Michael B. (1988)
Previous observations of OClO over the Antarctic obtained in 1986 are used to constrain the stratospheric abundance of bromine. The observed diurnal variation is consistent with the production of OClO via the reaction of ClO with BrO if the branching ratio to the BrCl channel is between 3.5 and 14 percent. Otherwise, an additional source in twilight is indicated. The present results suggest a stratospheric bromine concentration of 16 + or - 4 pptv, a value which is consistent with independent measurements.